Comparative Analysis of the Antioxidant and Antidiabetic Potential of Nelumbo nucifera Gaertn. and Nymphaea lotus L. var. pubescens (Willd.) - Tamlal Pokhrel; Dipesh Shrestha; Kamal Dhakal; Paras Mani Yadav; Achyut Adhikari (Journal of Chemistry)
Background. Nelumbo nucifera Gaertn. and Nymphaea lotus L. var. pubescens (Willd.) are both aquatic rhizomatous perennial plants mostly found in the tropical region of Nepal, India, Bangladesh, China, and Eastern Asia. Nymphaea pubescens and Nelumbo nucifera plants are famous for their different biological activities such as antidiabetic, antioxidant, hepatoprotective, antidiarrheal, and anti-inflammatory properties. Objective. The present study majorly focused on the determination of in vitro antioxidant and antidiabetic properties of Nelumbo nucifera and Nymphaea pubescens. Methods. In vitro α-glucosidase inhibition was performed using PNPG as a substrate. Antioxidant property of the plant extract was determined by DPPH free radical scavenging assay. The aluminium trichloride method was done for the estimation of total flavonoid content. Likewise, Folin–Ciocalteu reagent was used for determining total phenolic content. Results. The total phenolic content of N. nucifera and N. pubescens was found to be 172.827 ± 0.41 and 194.87 ± 0.93 mg GAE/g, respectively, while the total flavonoid content was reported 17.12 ± 1.04 and 34.59 ± 1.73 mg QE/g, respectively. The IC50 values of the crude extract and its fractions of N. nucifera against the DPPH free radical ranged from 33.46 ± 0.6 to 3.52 ± 0.09 μg/mL, while that of the N. pubescens ranged from 14.30 ± 0.43 to 1.43 ± 0.08 μg/mL. Similarly, for the in vitro α-glucosidase inhibition activity, the IC50 of the crude extract and its fractions of N. nucifera varied from 349.86 ± 2.91 to 29.06 ± 0.24 μg/mL and that of N. pubescens ranged from 224.4 ± 6.85 to 5.29 ± 0.39 μg/mL. Conclusion. Both aquatic plants N. nucifera and N. pubescens show antioxidant properties and can inhibit α-glucosidase in in vitro. Further research is required to identify the inhibiting compounds.